Synthesis, morphological structures and material characterization of electrospun PLA: PCL/magnetic nanoparticle composites for drug delivery - Haroosh, Hazim; Dong, Yu; Ingram, Gordon (John Wiley and Sons Inc, 2013)
The effects of pure and impure magnetic nanoparticles (MPs) with three different concentrations (0.01, 0.1 and 1 wt%/v) on the morphological structure, crystallinity level, thermal properties and constituent interactions of electrospun poly(lactic acid) (PLA): poly(e-caprolactone) (PCL) based composites were investigated by means of scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), differential scanning calorimetry (DSC), gel permeation chromatography (GPC), Fourier transform infrared spectroscopy (FTIR) and drug release tests using UV–vis spectrophotometry. Tetracycline hydrochloride (TCH), as a typical therapeutic compound, was loaded into these composite fibrous structures to study their application for drug delivery. The infrared spectra of composite nanofibers confirm the successful embedding of MPs into the fibrous networks. The addition of pure MPs increased the solution viscosity and thus promoted the MP dispersion inside the electrospun composite fiber mats. Impure MPs led to considerably lower average fiber diameters, and could generate unique cell structures that were reported for the first time in this study. The accelerated release of TCH was found by adding pure MPs to PLA: PCL blends. This characteristic was reflected in the parameters of Ritger-Peppas and Zeng models, which were well fitted to our experimental drug release data.